PSMA redirects MAPK to PI3K-AKT signaling to promote prostate cancer progression. (4th July 2017) - Caromile, Leslie Ann; Shapiro, Linda H.
ABSTRACT: Increased Prostate Specific Membrane Antigen expression promotes tumor progression in prostate epithelium by dysregulating the β1-integrin/type I insulin-like growth factor receptor axis, resulting in a shift in signaling from the less aggressive mitogen-activated protein kinase-extracellular signal-regulated kinases 1 and 2 pathway to the pro-survival protein kinase B(AKT)/phosphatidylinositol 3-kinase pathway.